THE IMPACT OF SOCIAL INFLUENCE AND PRODUCT QUALITY ATTRIBUTES TO CUSTOMER BUYING DECISION OF IPHONE IN MANADO - Rumate, Gina Paula (Universitas Sam Ratulangi, 2014)
Smartphone be the most desirable mobile phone in the world. Smartphone is a mobile device which is more than merely make and receive phones call, text message, and voice call. The function of smartphone, which not only can be used for make and receive call, text message, or take a picture, but also can be used like a small computer make people have been switching their mobile phone to smartphone. Many people switched their mobile phone to smartphone in Indonesia, made Indonesia was including in top 5 smartphone users in the world. There are 47 million smartphone users in Indonesia, and it will increase until 103, 7 million users in 2017. There are some factors which impact customer buying decision, some of them are social influence and product quality attributes. The main objective of this study is to determine the impact of social influence and product quality attributes to customer buying decision. Associative method is used by this study with technique analysis is multiple regression analysis. The populations of this study are all iPhone users in Manado and as the sample are 100 iPhone users in Manado. The result of this study infer that social influence and product quality attributes have impact to customer buying decision of iPhone users in Manado simultaneously. While partially, only social influence which has impact to customer buying decision. Social influence is impact customer buying decision significantly. This study suggests to the marketers that need to provide smartphone such as iPhone with good quality and up to date style. Because if the the product have good quality and up to date style customer will trust and interest with the product and et the end will decide to buy the product. Â Keywords: social influence, product quality attributes, buying decision